Exploring the Influence of Age at Menarche on Metabolic Syndrome and Its Components Across Different Women's Birth Cohorts - Maryam Farahmand; Maryam Mousavi; Fereidoun Azizi; Fahimeh Ramezani Tehrani (Endocrinology, Diabetes & Metabolism)
ABSTRACT Purpose Metabolic syndrome (MetS) is the primary cardiovascular risk factor, making it a global issue. Our objective was to assess the association between the age at menarche (AAM) and MetS and its components in different generations of women. Methods In this cross‐sectional study, 5500 eligible women aged ≥ 20 who participated in the Tehran lipid and glucose study in 2015–2017 were selected. Participants were divided into groups by birth cohorts (BC) (born ≤ 1959, 1960–1979, and ≥ 1980) and AAM (≤ 11, 12–15, and ≥ 16 years, early, normal, and late, respectively). The status of MetS and its components were compared amongst participants using logistic regression. Results Normal AAM (12–15 years) was considered the reference group. The adjusted model revealed that AAM ≤ 11 is associated with a higher risk of 34% (95% confidence interval (CI): 1.04, 1.71) in MetS, and the prevalence of MetS in the early menarche group was higher in BCI, and BCII (odds ratio (OR): 1.87; 95% CI: 1.04, 3.36 and OR: 1.33; 95% CI: 1.00, 1.89, respectively). Those with late menarche demonstrated a lower risk (OR:0.72; 95% CI: 0.57, 0.91) of abdominal obesity, and early menarche showed a higher risk (OR: 1.45; CI: 1.14, 1.86). This higher risk in early menarche was observed in BCI and BCII (OR: 1.76; 95% CI: 1.16, 2.66 and OR: 1.80; 95% CI: 1.23, 2.64, respectively). However, the protective effect of late menarche was observed in BC II and BC III (OR: 0.74; 95% CI: 0.54, 1.00 and OR: 0.64; 95% CI: 0.44, 0.96, respectively). Conclusions The influential effect of AAM on metabolic disturbances varies amongst different generations.